« Récupérer le sexe qui m’a été volé » : la sexualité comme affirmation de soi chez Asaka Yûho - Anne-Lise Mithout (Genre, Sexualité et Société)
Asaka Yûho’s autobiography was the first account of a disabled woman’s sex life published in Japan. The text, written from an activist’s perspective, intends both to condemn social barriers weighing upon disabled people’s sexuality in Japan, and to narrate the author’s individual struggle for romantic and sexual fulfillment. For Asaka Yûho, sexuality is one key for disabled people’s self-assertion and fight for recognition. This paper is aimed at analyzing the interconnections between sexuality and identity suggested in her work. On the one hand, it highlights how the Japanese social environment gives structure (and limitations) to the construction of disabled women’s sexual identity. On the other hand, by studying Asaka Yûho’s personal case, it shows how an individual can, over time, make use of some room for maneuver to negotiate and rebuild his/her identity, sexuality potentially playing a key role in the reconstruction of a wounded identity.